The socio-spatial distribution of migrants in German cities between 2014 and 2017 - Stefanie Jähnen; Marcel Helbig (Geografiska Annaler: Series B, Human Geography, 2023)
In recent years, Germany has taken in large numbers of immigrants. We look at the places where those migrants have settled in German cities. Our focus is on their socio-spatial distribution: To what extent is the social structure of neighbourhoods associated with the influx of migrants into those neighbourhoods? Our analysis draws on data on 86 large and medium-sized German cities with a total of 3770 neighbourhoods. Using linear (multi-level) regression models, we analyze the relation between the evolution of the proportion of foreigners in these neighbourhoods between 2014 and 2017 and the neighbourhoods' social structure in 2014. We find that the proportion of foreigners has increased much more strongly in the most socially disadvantaged neighbourhoods – especially in East Germany. A detailed examination of the individual cities reveals pronounced geographical disparities. The differences between the cities may be partially explained by vacancy rates and municipal tax revenues.
Keywords: 320; Inequality; immigration; neighbourhood; segregation